2002
DOI: 10.1897/1551-5028(2002)021<0493:tiorpo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Redox Potential on the Degradation of Halogenated Methanes

Abstract: To determine the influence of redox potential on the reaction mechanism and to quantify kinetics of the dechlorination by digester sludge, the test compounds trichlorofluoromethane (CFCl3), carbon tetrachloride (CCl4), and chloroform (CHCl3) were incubated in the presence of sludge and variable concentrations of reducing agent. Different sources of dehalogenation were examined, including live sludge and heat-killed sludge, and abiotic mechanisms were quantified in the absence of sludge. Batch incubations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Like corrinoids, another reduced porphyrinogen coenzyme, hematin, has been shown to catalyze the reduction of CFC-11 (Lovley & Woodward 1992) and CFC-113 (Lesage et al 1992). Heat-killed cells of anaerobic sludge supplied with the bulk reductant Ti(III)citrate also catalyzed the abiotic reduction of CFC-11 as was observed with the purified coenzymes (Olivas et al 2002). Cytochrome P450 monooxygenase is well known for carry out oxidative reactions; however, in the absence of elemental oxygen the reduced heme group can transfer its electrons to halogenated organics (Li & Wackett 1993).…”
Section: Microbiology and Biochemistry Of Cfc Biodegradationmentioning
confidence: 85%
See 1 more Smart Citation
“…Like corrinoids, another reduced porphyrinogen coenzyme, hematin, has been shown to catalyze the reduction of CFC-11 (Lovley & Woodward 1992) and CFC-113 (Lesage et al 1992). Heat-killed cells of anaerobic sludge supplied with the bulk reductant Ti(III)citrate also catalyzed the abiotic reduction of CFC-11 as was observed with the purified coenzymes (Olivas et al 2002). Cytochrome P450 monooxygenase is well known for carry out oxidative reactions; however, in the absence of elemental oxygen the reduced heme group can transfer its electrons to halogenated organics (Li & Wackett 1993).…”
Section: Microbiology and Biochemistry Of Cfc Biodegradationmentioning
confidence: 85%
“…Also methanogenic landfill leachate samples were shown to degrade CT (Kromann et al 1998). Both CT and CF are readily biotransformed by unadapted methanogenic sludge from various sources (Yu & Smith 1997;van Eekert et al 1998;Olivas et al 2002).…”
Section: Microbiology and Biochemistry Of Lower Chlorinated Methane Bmentioning
confidence: 99%
“…SO 4 2À also limited the decrease in the redox potential in soil with increasing incubation time because of its oxidizing properties. The redox potential is an environmental parameter that affects oxidationereduction and reductive dechlorination of halogenated organic pollutants (Bagramyan et al, 2000;Olivas et al, 2002). The reduction of Fe(III) in the lower soil layers was also considered as an inhibitor for competition electron donors with PCP.…”
Section: Pcp Dissipation In the Surface And Deep Layers Of Soil Profilesmentioning
confidence: 99%
“…Several studies have shown that low redox potentials are required for dechlorination (Pardue et al, 1988, Masscheleyn et al, 1991, Schumacher et al, 1997, Stuart et al, 1999, Arnold and Roberts, 2000, Olivas et al, 2002and Shimomura and Sanford, 2005. The highest rates of dechlorination were observed at lowest redox potentials tested (E Ag/AgCl = −348 mV) ( Olivas et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…The highest rates of dechlorination were observed at lowest redox potentials tested (E Ag/AgCl = −348 mV) ( Olivas et al, 2002). Shulder (2006) noted that redox potential measurements can be an effective control parameter for maintaining an oxidizing, or reducing environment.…”
Section: Introductionmentioning
confidence: 99%